2010
DOI: 10.1155/2010/608680
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Menthol in Beeswax by a Supercritical Fluid Technique

Abstract: Encapsulation of menthol in beeswax was prepared by a modified particles from gas-saturated solutions (PGSS) process with controlling the gas-saturated solution flow rate. Menthol/beeswax particles with size in the range of 2-50 μm were produced. The effects of the process conditions, namely, the pre-expansion pressure, pre-expansion temperature, gas-saturated solution flow rate, and menthol composition, on the particle size, particle size distribution, and menthol encapsulation rate were investigated. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…The resulting saturated solution is rapidly expanded through a tiny nozzle using moderate pressure which leads to reduction in temperature and the formation of particles due to the cooling effect. Zhu and colleagues [87] encapsulated menthol in beeswax using the PGSS.…”
Section: Supercritical Fluids (Scf)mentioning
confidence: 99%
“…The resulting saturated solution is rapidly expanded through a tiny nozzle using moderate pressure which leads to reduction in temperature and the formation of particles due to the cooling effect. Zhu and colleagues [87] encapsulated menthol in beeswax using the PGSS.…”
Section: Supercritical Fluids (Scf)mentioning
confidence: 99%
“…Equipped with an 80-μm-diameter nozzle and under the same pre-expansion conditions, the same authors showed less attractive results from lipid particles synthesized with beeswax and menthol. A multimodal population of particles ranging from 45 to 180 μm was obtained [ 100 ]. By application of similar conditions, Sampaio de Sousa and colleagues [ 62 ] achieved glyceryl monostearate microparticles of about 5 μm loaded with caffeine, though, owing to the hydrophilicity of caffeine, it was necessary to use water as co-solvent.…”
Section: Reviewmentioning
confidence: 99%
“…7,8 However, spray-dried microcapsules tend to have a wide particle size distribution and a high surface drug residue rate, which limits their practical application. In addition to the two aforementioned methods, Lan et al 9 encapsulated menthol by beeswax using a supercritical fluid approach. The as-prepared menthol/beeswax microcapsules protected menthol from volatilization loss.…”
Section: Introductionmentioning
confidence: 99%